2018
DOI: 10.1111/1744-7941.12199
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance work system and employee performance: the mediating roles of social exchange and thriving and the moderating effect of employee proactive personality

Abstract: Research on high‐performance work systems (HPWS) has drawn primarily from social exchange theory and human capital theory to unlock the underlying mechanisms in relation to employee performance. In addition to social exchange and human capital theory, a personal resources perspective can also be used to explain the effects of HPWS. In this cross‐level research, we examined the mediating roles of social exchange and thriving, and the moderating effect of proactive personality in the relationships between HPWS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 89 publications
(217 reference statements)
5
70
0
1
Order By: Relevance
“…Accordant with the COR theory POS is an esteem foundation that strengthen employee self-confidence for survival of professional working demands (Lazarus, 1991). Moreover, COR theory, clarifies that how HPWP contribute to the behavior and performance; and how individuals maintain, protect, devote and build their resources for the better utilization during the work (Zhang et al, 2018;Zhang et al, 2019). In the light of COR theory, we investigate the moderating role of PPC in the relationship of HPWP and OCB.…”
Section: Theoretical Framework and Proposed Research Modelmentioning
confidence: 91%
See 2 more Smart Citations
“…Accordant with the COR theory POS is an esteem foundation that strengthen employee self-confidence for survival of professional working demands (Lazarus, 1991). Moreover, COR theory, clarifies that how HPWP contribute to the behavior and performance; and how individuals maintain, protect, devote and build their resources for the better utilization during the work (Zhang et al, 2018;Zhang et al, 2019). In the light of COR theory, we investigate the moderating role of PPC in the relationship of HPWP and OCB.…”
Section: Theoretical Framework and Proposed Research Modelmentioning
confidence: 91%
“…Therefore, according to this theory we investigate the relationship between independent variable 'HPWP' and dependent variable 'TP and IRP'. Moreover, from the view point of social exchange theory, when employees realize about the organizational and managerial interest towards them like; HPWP and organizational support to improve their skills, abilities, competencies, motivation, knowledge; as a result employees pay back by adopting good attitude towards their job and enhance their skills and spirit for the OCB (Ahmad, Ismail, Amin, & Ramzan, 2012;Aktar & Pangil, 2017;Claudia, 2018;Gong et al, 2010;Vu, 2018;Zhang et al, 2019). In the same way, according to Colquitt et al (2014), a longterm and socio-emotional exchange association is describes by commitment, responsibility, and reciprocal trust among employees and organizations.…”
Section: Theoretical Framework and Proposed Research Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang [38] demonstrated that an employee's proactive personality plays a moderating role between the LMX relationship and employee creativity through empirical studies, as well as between the LMX relationship and insider identity cognition. Through a multilevel analysis, Zhang [39] found that social exchange and social development play a mediating role between a high-performance work system (HPWS) and employee task performance, as well as HPWS and organizational citizenship behavior. Proactive personality was found to attenuate HPWS's direct effect on the ability to thrive and indirect effects on employee task performance and organizational citizenship behaviors (OCBs) through thriving.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that proactive personality is a personal factor that facilitates helping behavior [ 24 , 26 ]. Employees with a proactive personality are more likely to make positive inferences about their work environment [ 27 ]. Drawing on the existing literature, we expect that proactive personality moderates the relationship between trust in coworkers and helping behavior.…”
Section: Introductionmentioning
confidence: 99%